Taking sides : clashing views on legal issues, 14th expanded edition - Katsh, M. Ethan ([S.l.] : McGraw-Hill, 2010)
Taking Sides volumes present current controversial issues in a debate-style format designed to stimulate student interest and develop critical thinking skills. Each issue is thoughtfully framed with an issue summary, an issue introduction, and a postscript or challenge questions. Taking Sides readers feature an annotated listing of selected World Wide Web sites. An online Instructor$1 (Bs Resource Guide with testing material is available for each volume. Using Taking Sides in the Classroom is also an excellent instructor resource. Visit www.mhhe.com/takingsides for more details.s
Keywords: Constitutional law; Justice, Administration of; Law; Law--Social aspects; Political questions and judicial power; United States